EMERGING SECURITY ARCHITECTURE IN ASIA PACIFIC: IMPACT ON PAKISTAN - Muhammad Nawaz Khan (Margalla Papers, 2025)
The evolving security paradigm in the Asia-Pacific is closely tied to the intensification of great power rivalry. Many nations are pursuing hedging strategies to protect their interests and guard against the fallout of the competition between major powers. A new equation has emerged with China’s ascent on the world stage, positioning Asia to become the hub of geopolitics. The United States (US) views China’s rise and Russia’s resurgence as challenges to its dominance in a unipolar world. Washington is establishing a security arc, evident in initiatives such as AUKUS, QUAD, Squad, and others, across the Asia-Pacific and beyond, in partnership with its Asian and Oceanian/Pacific allies to counter Beijing’s rise. The US Strategic Defence documents (National Security Strategy 2017, National Defense Strategy 2018, and Indo-Pacific Strategy 2022) have already emphasised the containment of China through the militarisation of Asia-Pacific. It also alluded to the transferring of critical technologies and growth in foreign alliances and regional partnerships. Washington’s repositioning in the region and its support for India as a net security provider in the Indian Ocean and beyond, through defence cooperation, have heightened concerns for Pakistan, which is already situated in a challenging geostrategic neighbourhood and has contentious relations with its eastern neighbour, India. Moreover, the US has accorded India a prominent position at the regional and global level to enforce its great power ambitions in the future. This will have far-reaching implications for Pakistan. The paper employs a qualitative research method based on a secondary assessment of academic sources.